716 mV Open‐Circuit Voltage with Fully Screen‐Printed p‐Type Back Junction Solar Cells Featuring an Aluminum Front Grid and a Passivating Polysilicon on Oxide Contact at the Rear Side. Issue 1 (6th December 2020) - Min, Byungsul; Wehmeier, Nadine; Brendemuehl, Till; Haase, Felix; Larionova, Yevgeniya; Nasebandt, Lasse; Schulte-Huxel, Henning; Peibst, Robby; Brendel, Rolf
Abstract : This article reports the recent progress of p ‐type back junction solar cells featuring an aluminum front grid and an n + ‐type passivating polysilicon on oxide (POLO) contact at the cell rear side. The best cell has an efficiency of 22.6% and an open‐circuit voltage of 716 mV, independently confirmed by Institute for Solar Energy Research Hamelin (ISFH) CalTeC. The cell area is 244.5 cm 2 . The increase in the SiN x capping layer thickness at the cell rear side reduces the deterioration of passivation quality of the POLO contact by screen‐printed silver. This increases the open‐circuit voltage by 22 mV compared with cells with a thinner nitride layer thickness. The investigation with scanning electron microscopy shows that the damage of the POLO contacts underneath the screen‐printed metal contacts is avoided by increasing the SiN x capping layer thickness. A contact resistivity of 2 mΩ cm 2 is measured using the transfer length method. Abstract : For the industrialization of poly‐Si‐based passivating contacts, it is crucial to ensure proper contact formation between screen‐printed silver and poly‐Si passivating contacts while maintaining the passivation quality. Herein, the possibility to reduce the deterioration of passivating contacts by adjusting the SiN x capping layer thickness is reported.